Recurrence Predictors in Operated Cases of Craniopharyngioma (Nepal Journal of Neuroscience, 2026)
Background: Craniopharyngiomas are benign tumors that develop in the sellar and suprasellar region of the brain. Their location often leads to significant health complications due to the pressure exerted on nearby critical structures. Surgical removal remains the cornerstone of treatment. One of the major challenges is the high rate of recurrence, which affects approximately 30% to 40% of patients, even after seemingly successful surgery. Gaining these insights of causes of recurrence is crucial for guiding treatment choices and planning effective long-term follow-up care.Objectives: To identify the recurrence predictors of craniopharyngioma and correlate it with other factors.Methods: This observational study was carried out at a tertiary care center over a four-year period, from January 2020 to January 2024 that included 25 patients who underwent surgical removal of craniopharyngiomas. Based on their postoperative follow-up, patients were divided into two groups: those who experienced tumor recurrence and those who did not. Data were collected based on each patient’s demographics, symptoms, imaging findings, tumor subtype, and the presence of β-catenin expression through immunohistochemistry.Results: In this study, the overall recurrence rate of craniopharyngiomas was 40%. Recurrence was notably higher in certain subgroups like in males (68%). Tumors with calcifications on imaging were also more likely to recur (88%). A strong association was also observed between beta-catenin expression and the likelihood of recurrence. In contrast, no significant link was found between recurrence and factors such as gender, preoperative hormonal status.Conclusion: Our findings suggest that younger age at diagnosis, the presence of calcification are all significantly associated with a higher risk of tumor recurrence. Additionally, positive β-catenin immunoreactivity emerged as a potential biomarker for identifying tumors with more aggressive behavior.